Analysis of Human Standing Balance by Largest Lyapunov Exponent - Zahari, Taha; Kun, Liu; Wang, Hongrui; Xiao, Jinzhuang (Hindawi Publishing Corporation, 2015)
The purpose of this research is to analyse the relationship between nonlinear dynamic character and individuals’ standing balance by the largest Lyapunov exponent,which is regarded as a metric for assessing standing balance.According to previous study,the largest Lyapunov exponent from centre of pressure time series could not well quantify the human balance ability.In this research,two improvements were made.Firstly,an external stimulus was applied to feet in the form of continuous horizontal sinusoidal motion by a moving platform.Secondly,a multiaccelerometer subsystem was adopted.Twenty healthy volunteers participated in this experiment.A new metric,coordinated largest Lyapunov exponent was proposed,which reflected the relationship of body segments by integrating multidimensional largest Lyapunov exponent values.By using this metric in actual standing performance under sinusoidal stimulus,an obvious relationship between the new metric and the actual balance ability was found in the majority of the subjects.These results show that the sinusoidal stimulus can make human balance characteristics more obvious,which is beneficial to assess balance,and balance is determined by the ability of coordinating all body segments.